Biometric Based Personal Identification for Cashless Payment Systems in Gym Memberships - Alya Dwi Rahma; Very Kurnia Bakti; Abdul Basit (Universitas Malikussaleh, 2026)
The increasing consciousness regarding healthy living has triggered a marked rise in gym memberships. Nonetheless, most facilities still depend on traditional payment and documentation methods. The main issue associated with these outdated systems is their vulnerability to human mistakes, data redundancy, loss of physical records, and a significant deficiency in digital integration. Although the use of digital payment methods such as QRIS has expanded, these systems are still prone to fraudulent activities and delays. This research intends to create an organized, secure, and extremely effective membership and payment management system. The approach taken includes the design and execution of a software structure built on Near Field Communication (NFC) technology, which is directly linked to a payment gateway. The findings from the implementation indicate that the newly developed system effectively resolves traditional operational challenges. The NFC